Modelling interdependencies among critical infrastructures. (4th September 2008) - Robert, Benoit; De Calan, Renaud; Morabito, Luciano
Over the years, Critical Infrastructures (CIs) have become increasingly automated and interlinked. This linkage between CIs results in a very complex and dynamic system which increases their vulnerability to failures. In fact, interdependencies between CIs are a true means of propagation of hazards from one network to another. Thus, when an infrastructure is experiencing difficulties and failures, it can rapidly generate a cascading effect affecting the other infrastructures. Identifying, understanding and modelling these interdependencies is thus necessary to prevent these cascading effects. This paper presents a model developed to understand the interdependencies between CIs and to prevent cascading effects from happening. Based on the resources exchanged by CIs, this model allows the visualisation and the anticipation of domino effects in time and space, allowing CI managers to set up convenient preventive and protective measures in order to avoid their propagation.